2019
DOI: 10.1136/bmjgh-2019-001705
|View full text |Cite
|
Sign up to set email alerts
|

Insulin price components: case studies in six low/middle-income countries

Abstract: IntroductionUnderstanding price components for insulin products can help design interventions to improve insulin affordability in low/middle-income countries.MethodsAn adapted WHO/Health Action International standardised methodology was used in Brazil (Rio de Janeiro), China (Hubei and Shaanxi Provinces), Ghana, India (Haryana State), Indonesia and Uganda. Selected insulin products had their prices traced backwards through the supply chain from public and private sector retail outlets in the capital city and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This change in practice has an impact on the cost of diabetes management for both the individual and the health system. In addition, pricing policies and mark-ups within the health system and supply chain affect the overall financial burden of diabetes management [ 6 , 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change in practice has an impact on the cost of diabetes management for both the individual and the health system. In addition, pricing policies and mark-ups within the health system and supply chain affect the overall financial burden of diabetes management [ 6 , 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These mark-ups also apply at different stages of the supply system in the private sector. Ball et al [ 33 ] found that these mark-ups cumulatively equalled 8.7–47.7% of the manufacturer’s selling price for locally produced insulin and 10.0%–565.8% for imported insulins. It is important to note that, beyond price, a variety of geographical and health system factors can have an impact on access to insulin, such as distance of the patient to healthcare facilities [ 31 ].…”
Section: Global Barriers To Insulin Accessmentioning
confidence: 99%
“…205 However, affordability for individuals remains a challenge in many settings with cumulative markups ranging from 8.7% to 565.8%. 206 In many LMICs, the price of insulin is paid for by the individual or, in some contexts, subsidies are in place. By contrast, in most HICs, various government-funded or health insurance schemes provide some form of financial protection, either ensuring that insulin is provided for free to the individual or, at least, that the person does not bear the full cost.…”
Section: Quality Of Care Structure Of Care Processes Of Care and Outc...mentioning
confidence: 99%
“…Given the reduced incidence of hypoglycemia, newer analogs may be even more cost‐effective 205 . However, affordability for individuals remains a challenge in many settings with cumulative markups ranging from 8.7% to 565.8% 206 . In many LMICs, the price of insulin is paid for by the individual or, in some contexts, subsidies are in place.…”
Section: Balancing Costs and Benefits In Diabetes Carementioning
confidence: 99%
“…Case studies in six LMICs found mark‐ups on insulin ranging from 8.7% to 565.8% depending on the country, sector and region within the country. The proportion of the final price attributed to the manufacturer's selling price varied from 15.0% to 92.0% 17 . A key issue is that many LMICs do not regulate mark‐ups in the supply chain nor control medicine prices.…”
Section: Issues Impacting Access To Insulinmentioning
confidence: 99%